Soliton Dynamics and Modulation Instability in the (3+1)-Dimensional Generalized Fractional Kadomtsev–Petviashvili Equation - Alharthi, Nadiyah Hussain; Kaplan, Melike; Alqahtani, Rubayyi T. (MDPI AG, 2025)
In this article, novel methods of analysis to solve the (3+1)-dimensional generalized fractional Kadomtsev–Petviashvili equation, which plays a crucial role in the modelling of fluid dynamics, particularly wave propagation in complicated media, are presented. The fractional KP equation, a well-established mathematical model, uses fractional derivatives to more adequately describe more general types of nonlinear wave phenomena, with a richer and improved understanding of the dynamics of fluids with non-classical characteristics, such as anomalous diffusion or long-range interactions. Two efficient methods, the exponential rational function technique (ERFT) and the generalized Kudryashov technique (GKT), have been applied to find exact travelling solutions describing soliton behaviour. Solitons, localized waveforms that do not deform during propagation, are central to the dynamics of waves in fluid systems. The characteristics of the obtained results are explored in depth and presented both by three-dimensional plots and by two-dimensional contour plots. Plots provide an explicit picture of how the solitons evolve in space and time and provide insight into the underlying physical phenomena. We also added modulation instability. Our analysis of modulation instability further underscores the robustness and physical relevance of the obtained solutions, bridging theoretical advancements with observable phenomena.